Small axe : five films by Steve McQueen [videorecording (Blu-Ray)] - McQueen, Steve, 1969-; Newland, Courttia; Siddons, Alastair; Lenkiewicz, Rebecca; Ackie, Naomi; Best, Khali; Barry, Neal; Beadle, Gary; Bovell, Dennis; Wright, Letitia, 1993-; Kirby, Malachi, 1989-; Parkes, Shaun; et al. (Criterion collection, 2023)
Five original films, set between 1969 and 1982, celebrate the courage and solidarity of London's West Indian community. From a group of activists taking on a seemingly hopeless battle against police persecution, to a teenager experiencing a blues party full of dance, danger and romance, they're a powerful reminder of how brave individuals can spark change.